Giant Chondroid Lipoma of Breast - Jorwekar, G. J. (Springer-Verlag, 2012)
Lipomas are benign tumors composed of mature fat, usually encapsulated. Vast majority of lipomas are small, weighing only a few grams, and grow slowly. Lipoma occur rarely in breast causing diagnostic dilemma. Chondroid lipoma is a rare variant of lipoma which is benign in nature. We present a case of 65 year old female patient presented with lump in right breast, underwent surgical excision and histopathology reported as chondroid lipoma.